Antioxidant Effects of Brown Algae Sargassum on Sperm Parameters: CONSORT-Compliant Article. Issue 52 (December 2015) - Sobhani, Alireza; Eftekhaari, Tasnim Eghbal; Shahrzad, Mohammad Esmaeil; Natami, Mohammad; Fallahi, Soghra
Abstract : Abstract: The occurrence of oxidative stress during the sperm freeze-thaw cycles affects the sperm parameters and eventually leads to a decrease in its reproductive potential. Sperm protection against oxidative reactions during freezing is done by antioxidants. Since the selection of a suitable sperm cryopreservation bank is effective in maintaining acceptable reproductive potential and motility of sperm during cryopreservation. This study aimed to evaluate the antioxidant effects of different doses of the extract of brown algae Sargassum on oxidative stress and frozen human sperm parameters. We conducted a randomized controlled trial on the semen samples from 11 healthy men in the age group of 25 to 36 years. The samples were collected by masturbation after 3 to 5 days of abstinence from ejaculation. The specimens were divided into 3 equal parts, including 1 control group and 2 experimental groups. The 2 experimental groups were frozen using the rapid solidification technique with Sargassum extract at doses of 250 and 500 μg/mL. Motility and morphology of sperms were measured using a computer system and CASA software and the amount of reactive oxygen species was determined using Oxisperm kit. Sargassum extract significantly decreased the amount of reactive oxygen species ( P < 0.005) and at doses of 250 and 500 μg/mL, significantly increased the overall motility ( P < 0.006) and progressive motility ( P < 0.007) after solidification, but did not affect the normal morphology of sperms. The addition of ethanol extract of Sargassum prevents reactive oxygen species production during the solidification process and improves sperm motility at doses of 250 and 500 μg/mL.